Weibull Mortality Tables based on Indonesian Mortality Table 2019 - Dei Alibazah, Terra; Prabowo, Agung; Hendriva Guswanto, Bambang (Communication In Research And Publications, 2023)
Life tables are used to calculate the probability that a member of a population for each age group in a certain country would survive until the next year and die before the next year. A life table could be constructed based on another life table using a mortality law. This study will construct a Weibull Life Table based on the 2019 Indonesian Life Table using Weibull’s mortality law, with its parameters estimated using the Ordinary Least Squares method. The results of this study show that the oldest age in the male Weibull Life Table is 115 years, which is 4 years older than the oldest age in the male 2019 Indonesian Life Table. The oldest age in the female Weibull Life Table is 119 years, which is 8 years older than the older age in the female 2019 Indonesian Life Table.